Influence of Cash Flow and Net Profit on Stock Price - Fatmawatie, Naning (Department of Islamic Accounting, The Faculty of Islamic Economics and Business, State Islamic Institute of Kediri [IAIN Kediri, 2023)
The value of the company will be reflected in its share price, so the stock price can be said to be a measure of the company's success. In addition, it can also be seen through the condition of profits and cash flow turnover. The better the company's performance, the share price will increase, so it is natural for issuers to maintain their share prices because they reflect the actual condition of the company. This study aims to analyze the effect of operating cash flow, investment cash flow, funding cash flow, and net income on stock prices. This type of research is quantitative associative. The population in this study is the financial statements of the company Kalbe Farma Tbk. the 2013-2020 period, while the samples taken are all financial reports at the company Kalbe Farma Tbk. period 2013-2020 and the sampling was taken through a saturated sample (non-purposive sampling). The results of this study indicate that partially and simultaneously the variables of operating cash flow, investment cash flow, funding cash flow, and net income do not affect stock prices. This study does not support the theory put forward by Wetson and Bridgham, that the higher the earnings per share provided by the company, the higher the return. Harga saham adalah salah satu ukuran keberhasilan perusahaan karena merupakan cerminan dari nilai perusahaan. Selain harga saham, keberhasilan juga dapat dilihat melalui kondisi laba dan perputaran arus kas. Semakin baik kinerja perusahaan, maka harga saham akan meningkat. Penelitian ini bertujuan untuk menganalisis pengaruh arus kas operasi, arus kas investasi, arus kas pendanaan, dan laba bersih terhadap harga saham. Jenis penelitian ini adalah kuantitatif-asosiatif. Populasi dalam penelitian ini adalah laporan keuangan perusahaan Kalbe Farma Tbk. periode 2013-2020, sedangkan sampel yang diambil adalah seluruh laporan keuangan perusahaan Kalbe Farma Tbk. periode 2013-2020 dan pengambilan sampel diambil melalui sampel jenuh (non-purposive sampling). Hasil penelitian ini menunjukkan bahwa secara parsial dan simultan variabel arus kas operasi, arus kas investasi, arus kas pendanaan, dan laba bersih tidak mempengaruhi harga saham. Penelitian ini tidak mendukung teori yang dikemukakan oleh Wetson dan Bridgham, bahwa semakin tinggi laba per saham yang diberikan oleh perusahaan, semakin tinggi pengembaliannya.